The Cell Polarity Protein Scribble Is Involved in Maintaining the Structure of Neuromuscular Junctions, the Expression of Myosin Heavy Chain Genes, and Endocytic Recycling in Adult Skeletal Muscle Fibers - Gessler, Lea; Jian, Yongzhi; Ngo, Nam Anh; Hashemolhosseini, Said (Cells, 2025)
The role of LAP proteins expressed in skeletal muscles (ERBIN, LANO, and SCRIBBLE) and at neuromuscular junctions (NMJs) remains largely unknown. Our previous data demonstrate that LAP proteins are differentially expressed in muscle cells, nerve endings, and terminal Schwann cells, though they are all expressed in myofibers and accumulate at NMJs. ERBIN and SCRIBBLE align with acetylcholine receptor clusters (CHRNs) at the NMJ. In vivo ablation of Erbin is associated with smaller CHRN and upregulation of Lano and Scribble. However, SCRIBBLE was also shown to influence the fate decision of muscle stem cells. Here, we investigated how the absence of SCRIBBLE in skeletal muscle cells might impair skeletal muscle fibers or NMJs. Although conditional Scribble knockout mice did not exhibit changes in weight or viability, force per weight decreased slightly. This was supported by compromised neuromuscular transmission and increased NMJ fragmentation. Moreover, Scribble knockout muscles transcribe less myosin heavy chain genes. Here, we also showed that RAB5, an effector of endocytic recycling, interacts with all LAP proteins, but in Scribble knockout muscles, reduced interaction was detected with ERBIN and LANO. These data suggest that a delicate signaling network employing LAP proteins is necessary for skeletal muscle fibers and NMJs.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Erbin; Lano; LAP; neuromuscular junction; Scrib; Scribble; skeletal muscle